2019
DOI: 10.1111/cogs.12768
|View full text |Cite
|
Sign up to set email alerts
|

Speech Planning at Turn Transitions in Dialog Is Associated With Increased Processing Load

Abstract: Speech planning is a sophisticated process. In dialog, it regularly starts in overlap with an incoming turn by a conversation partner. We show that planning spoken responses in overlap with incoming turns is associated with higher processing load than planning in silence. In a dialogic experiment, participants took turns with a confederate describing lists of objects. The confederate’s utterances (to which participants responded) were pre‐recorded and varied in whether they ended in a verb or an object noun an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 76 publications
1
33
0
1
Order By: Relevance
“…While naming latencies in the presented experiments are generally longer than average turn-transition times in conversational settings, the attested effects can be taken as informative about the processes of speech planning in conversation, where context, topic familiarity, predictable sequences of actions and the like speed up turn taking. The presented results support models of the psycholinguistics of dialogue that model response planning as taking place as early as possible (Heldner & Edlund, 2010;Levinson & Torreira, 2015), showing that early planning at least includes the stages of conceptual planning and formulation, even though processing costs in response preparation are higher in overlap with the incoming turn than during the silence between turns (Barthel & Sauppe, 2019). A recent study by Bögels and Levinson (in prep.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While naming latencies in the presented experiments are generally longer than average turn-transition times in conversational settings, the attested effects can be taken as informative about the processes of speech planning in conversation, where context, topic familiarity, predictable sequences of actions and the like speed up turn taking. The presented results support models of the psycholinguistics of dialogue that model response planning as taking place as early as possible (Heldner & Edlund, 2010;Levinson & Torreira, 2015), showing that early planning at least includes the stages of conceptual planning and formulation, even though processing costs in response preparation are higher in overlap with the incoming turn than during the silence between turns (Barthel & Sauppe, 2019). A recent study by Bögels and Levinson (in prep.…”
Section: Discussionsupporting
confidence: 81%
“…While a number of studies have shown that next speakers initiate planning in overlap, they did not investigate which steps of response preparation are run through while the current turn is still coming in and potentially interfering with simultaneously running planning processes. Planning in overlap comes at the cost of increased processing load (Barthel & Sauppe, 2019), which might cause next speakers to postpone certain processing stages until the end of the incoming turn in order to avoid high peaks in processing load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a recent study on turn-taking (Barthel & Sauppe, 2019) showed that production planning led to higher processing load (as measured by pupillary responses) when it started in overlap with the current turn than when it could only start when that turn had finished.…”
Section: Intermediate Model?mentioning
confidence: 93%
“…Such overlap may be problematic given that language production (planning) and comprehension rely on largely the same cognitive and neuronal architecture (e.g., Segaert, Menenti, Weber, Petersson, & Hagoort, 2012) and both processes have been shown to require central attention (e.g., Kubose et al, 2006;Shitova, Roelofs, Coughler, & Schriefers, 2017). Indeed, dual tasking with two linguistic tasks leads to more interference than when one of the tasks is non-linguistic (Fairs, Bögels, & Meyer, 2018), and production planning in turn-taking happening in overlap with concurrent speech input leads to increased processing load as compared to planning 'in the clear', as measured by pupillary responses (Barthel & Sauppe, 2019). Thus, one might predict that interlocutors attempt to keep the amount of overlap between comprehension and production minimal, that is, start planning as late as possible.…”
Section: Amentioning
confidence: 99%